The Welfare Effects of Farm Household Activity Choices in Post-War Mozambique - Tilman Brück (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper analyses the effects of activity choices on farm household income and consumption in a war-affected developing country. The study uses household survey data from Mozambique and controls for the endogeneity of activity choices with instrumental variables. War-time activity choices (such as subsistence farming) are shown to enhance welfare in the post-war period. Market and social exchange induce only limited welfare gains. Cotton adoption reduces household welfare, which contradicts previous studies not controlling for endogenous activity choices. The study thus demonstrates how standard predictions of economics may become invalid in post-war economies. Furthermore, the paper identifies pro-poor reconstruction policies.
Keywords: O13; I31; Q12; 330; poverty; farm households; activity choices; rural development; war; reconstruction; Landwirtschaftlicher Familienbetrieb; Haushaltsökonomik; Subsistenzwirtschaft; Wohlfahrtseffekt; Kriegsschaden; Schätzung; Mozambique